Excitonic quasimolecules containing of two quantum dots (JOURNAL OF ADVANCES IN PHYSICS, 2016)
The possibility of occurrence of the excitonic  quasimolecule formed of spatially separated electrons and holes in a nanosystem that consists  of CuO quantum dots synthesized in a silicate glass matrix. It is shown that the major contribution to the excitonic quasimolecule binding energy is made by the energy of the exchange interaction of electrons with holes and this contribution is much more substantial than the contribution of the energy of Coulomb interaction between the electrons and holes.